82.5k views
5 votes
Can someone explain the quadratic formula real quick lol

Can someone explain the quadratic formula real quick lol-example-1
User Dbmitch
by
5.2k points

2 Answers

1 vote

Answer:

D.x = (-3±√-7) / 2

Explanation:

We have given a quadratic equation.

x²+3x+4 = 0

From above equation, a = 1, b = 3 and c = 4

We have to find the solution of given equation bu using quadratic formula.

x = (-b±√b²-4ac) / 2a

Putting given values in above formula, we have

x = (-3±√(3)²-4(1)(4) ) / 2(1)

x = (-3±√9-16) / 2

x = (-3±√-7) / 2 which is the answer.

User Hdort
by
5.4k points
2 votes

Answer: OPTION D

Explanation:

THe quadratic formula is shown below:


x=(-b\±√(b^2-4ac))/(2a)

Given the quadratic equation shown in the image, you have that:

a=1

b=3

c=4

Therefore, when you susbtityte these values into the formula you obtain the following solution:


x=(-3\±√(3^2-4(1)(4)))/(2*1)


x=(-3\±√(-7))/(2)

User Mastupristi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.